Fire fighting pumping systems at industrial facilities - Nolan, Dennis P. (Noyes Publications, 1998)
This book describes fixed firewater pump installations for industrial facilities from the viewpoint of the end users, fire protection engineers, loss prevention professionals, and those just entering a career in which decisions about fire pump installations must be made. Therefore, much background information is given for the necessary requirements and usefulness of a firewater pump and the services that interface with it.